Pukis Cake Formulation Using Mocaf and Sesame Flour with the Addition of Red Spinach - Anggita Dwi Aulia; Tri Marta Fadhilah (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2026)
A probabilistic study on calcium deficiency among Indonesian adolescents indicates an insufficient average daily calcium intake of 290.4 mg. Consuming foods rich in calcium, such as sesame seeds and red spinach, can prevent calcium deficiency. This experimental study applied Completely Randomized Design with three formulations based on weight comparison of mocaf, sesame flour, and red spinach. Results showed that F3 had a slightly brown, distinct sesame aroma, sweet taste, and very soft texture, and achieved the highest organoleptic average score. The difference test results using the Kruskal-Wallis and Mann-Whitney tests revealed significant differences in the aroma, taste, and texture indicators. The hedonic test indicated that F2 was the most preferred by panelists (79.2%). Laboratory results showed that F3 had the highest levels of calcium (73.4 mg/100 g, equivalent to 6% ALG Value) and water content (33.9%), whereas F2 had the highest fat content (22.3%); however, the vitamin D content in F3 was almost undetectable (<0.005 mg/100 g). In conclusion, the modified pukis cake demonstrated acceptable organoleptic properties and an increased calcium content, although its calcium level remains below the threshold required to be classified as a calcium source, and its fat content exceeds the SNI-01-3840-1995 standard (maximum 3% per 100 g).